1990
DOI: 10.1007/bf00249181
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin-induced changes in the cell wall composition of Staphylococcus aureus before the onset of bacteriolysis

Abstract: To analyze if chemical cell wall alterations contribute to penicillin-induced bacteriolysis, changes in the amount, stability, and chemical composition of staphylococcal cell walls were investigated. All analyses were performed before onset of bacteriolysis i.e. during the first 60 min following addition of different penicillin G doses. Only a slight reduction of the amount of cell wall material incorporated after penicillin addition at the optimal lytic concentration was observed as compared to control cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
19
0
1

Year Published

1991
1991
2002
2002

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 19 publications
6
19
0
1
Order By: Relevance
“…It is noteworthy that no significant error arises from part of the wall label being held back in the cytoplasm, since fractionation of the labeled cells by the method of Park and Hancock (24) regularly showed that only less than 5% of the wall label resides in the cytoplasm from which it is lost to the growth medium at a rate of about 5% per generation time (36; see also references 5 and 29). Furthermore, boiling of the cells with 5% SDS did not solubilize any significant amount of the label, an observation that is in agreement with earlier results (29). Therefore, the release rate of the specific cell wall marker of [14C]N-acetylglucosamine from growing cells was measured in strains SG511, BB270, Col, and their femA mutants BB742, BB308, and BB403, respectively, to determine if inactivatingfemA had an effect on cell wall turnover.…”
Section: Resultssupporting
confidence: 87%
“…It is noteworthy that no significant error arises from part of the wall label being held back in the cytoplasm, since fractionation of the labeled cells by the method of Park and Hancock (24) regularly showed that only less than 5% of the wall label resides in the cytoplasm from which it is lost to the growth medium at a rate of about 5% per generation time (36; see also references 5 and 29). Furthermore, boiling of the cells with 5% SDS did not solubilize any significant amount of the label, an observation that is in agreement with earlier results (29). Therefore, the release rate of the specific cell wall marker of [14C]N-acetylglucosamine from growing cells was measured in strains SG511, BB270, Col, and their femA mutants BB742, BB308, and BB403, respectively, to determine if inactivatingfemA had an effect on cell wall turnover.…”
Section: Resultssupporting
confidence: 87%
“…This is in agreement with the results of previous studies in which exposure to concentrations of ␀-lactams below the MICs decreased O-acetylation of peptidoglycan in Neisseria gonorrhoeae, Proteus mirabilis, and Staphylococcus aureus (13,24,28). In conclusion, the results indicate that in L. casei ATCC 393, which is naturally resistant to glycopeptides, the tetralactate precursor is readily exported by the lipid transporter and, similarly to what was found in E. faecium expressing vancomycin resistance, well processed to be integrated in the peptidoglycan (8).…”
supporting
confidence: 93%
“…The fact that the concentration of this particular group of muropeptides remained unchanged in cells grown with or without antibiotic suggests that these compounds may have some special, essential function in the cell walls. Our findings confirm and extend the findings of earlier studies (5,6). Most recently, Snowden and Perkins (7) used a gel filtration technique to demonstrate changes in peptidoglycan composition when methicillin-susceptible staphylococci were grown in the presence of sub-MICs of various beta-lactam antibiotics.…”
supporting
confidence: 90%